THE EFFECT OF PERCEPTIONS OF EASE OF USE AND USEFULNESS ON IMPLEMENTATION OF SAK EMKM IN SMALL AND MEDIUM ENTERPRISES (UKM) IN POLEWALI - Wahyuni, Sry (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
ABSTRACT Purpose – The purpose of this study was to examine (1) the effect of perceived of Ease of Use, and (2) the effect of perceived usefulness on the implementation of SAK EMKM in Polewali. Design/methodology/approach – The theory used in this research is the Technology Accepted Model (TAM). Findings – The results of this study indicate: (1) perceived ease of use has a positive and significant effect on the implementation of SAK EMKM and (2) perceived usefulness has a positive and significant effect on the implementation of SAK EMKM. Originality – The population in this study were 132 small and medium enterprises in the city of Polewali Keywords: Technology Accepted Model (TAM), Perception of Ease of Use, Perception usefulness, Implementation of SAK EMKM Paper Type Research Result